Soft magnetic composite material and preparation method thereof, molded inductor
By pretreating and temperature-pressure treatment of soft magnetic composite materials, the problem of insufficient insulation resistance and pressurization density of soft magnetic composite materials in the prior art is solved, and the preparation of soft magnetic composite materials with high insulation resistance and high pressure density is realized, which is suitable for molded inductors in modern power electronic equipment.
Patent Information
- Application Number
- CN202210703275.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-21
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-06-21
AI Technical Summary
In the preparation of existing soft magnetic composite materials, due to uneven resin dispersion and poor coating of soft magnetic metal powder, the insulation resistance is reduced, making it difficult to meet the requirements of high insulation resistance and high voltage density at the same time.
By mixing the soft magnetic metal powder with a thermosetting resin system for granulation treatment, then pretreatment so that the resin state is between the initial state and the gel state, and then temperature-pressure treatment is performed to produce a soft magnetic composite material with high insulation resistance and high pressure density.
The coating effect of the thermosetting resin system on soft magnetic metal powder is improved, the viscosity of granulated powder is enhanced, and the soft magnetic composite material produced has high insulation resistance and compression density, meeting the stability requirements of modern power electronic equipment for molded inductance.
Smart Images

Figure GDA0005129339920000081 
Figure GDA0005129339920000082 
Figure GDA0005129339920000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrical components, and in particular to a soft magnetic composite material and a preparation method thereof, and a molded inductor. Background Art
[0002] As one of the key components in the field of modern power electronics, molded inductors are widely used in various power electronic equipment. With the popularization and application of electric vehicles, the Internet of Things, cloud servers, intelligent technologies and a new generation of semiconductor materials, the stability requirements of molded inductors are getting higher and higher, and the operating conditions of molded inductors are becoming more and more demanding, requiring the thermal stability of related molded inductors to be higher and higher. Therefore, improving the insulation resistance of molded inductors is a core issue in the technical development of such products.
[0003] Soft magnetic composite materials are composite materials with soft magnetic metal powder as the matrix and coated with at least one dielectric phase. Soft magnetic composite materials have lower eddy current loss, higher magnetic permeability, lower coercive force and higher insulation resistance. In addition, soft magnetic composite materials also have the advantages of three-dimensional anisotropy and easy machining, and are widely used in the preparation of molded inductors.
[0004] However, in the actual preparation of soft magnetic composite materials with thermosetting resin system as dielectric phase, the insulation resistance may be reduced due to uneven resin dispersion and poor coating of soft magnetic metal powder. Summary of the invention
[0005] The technical problem to be solved by the present invention is how to make the soft magnetic composite material and the molded inductor have high insulation resistance and pressing density at the same time.
[0006] In order to solve the above technical problems, the present invention provides a method for preparing a soft magnetic composite material, comprising the following steps:
[0007] The soft magnetic metal powder and the thermosetting resin system are mixed and then granulated to obtain granulated powder.
[0008] The granulated powder is pre-treated so that the state of the thermosetting resin system is between the initial state and the gel state, thereby obtaining the pre-gel state granulated powder.
[0009] The pre-gel granulated powder is subjected to temperature and pressure treatment to obtain a soft magnetic composite material.
[0010] In a feasible implementation, the viscosity of the pre-gel granulated powder is significantly increased compared to the initial state, and the pre-gel granulated powder can be transformed into a gel state within 5s-60s under the temperature of the warm-pressing treatment.
[0011] In a feasible implementation, the temperature of the pretreatment is 30°C-80°C lower than the temperature of the warm pressure treatment.
[0012] In a feasible implementation, the thermosetting resin system is bisphenol A cyanate ester and bisphenol A epoxy resin, the pretreatment temperature is 100° C.-140° C., and the pretreatment time is 30 min-120 min.
[0013] In a feasible implementation, the temperature of the warm-pressing treatment is 150° C.-200° C., and the time of the warm-pressing treatment is 15s-180s.
[0014] In a feasible implementation, the thermosetting resin system includes a thermosetting resin and a curing agent, wherein the thermosetting resin is selected from at least one of an epoxy resin, a cyanate resin and a linear phenolic resin.
[0015] In a feasible implementation, the soft magnetic metal powder is selected from carbonyl iron powder, reduced iron powder, atomized iron powder, atomized Fe (100-x-y) Si x Cr y At least one of powder (x=3.5-6.5, y=0.0-6.5), iron-based amorphous soft magnetic powder, iron-based amorphous nanocrystalline powder, Sandust powder and HighFlux powder.
[0016] In a feasible implementation, before the step of mixing the soft magnetic metal powder and the thermosetting resin system for granulation, the soft magnetic metal powder is subjected to surface insulation treatment.
[0017] The implementation of the present invention has the following beneficial effects:
[0018] The present invention obtains pre-gel state granulated powder by pre-treatment before subjecting the granulated powder to temperature and pressure treatment, thereby increasing the viscosity of the granulated powder under temperature and pressure treatment conditions, and improving the coating effect of the thermosetting resin system on the soft magnetic metal powder, thereby obtaining a soft magnetic composite material with higher insulation resistance. In the method, the thermosetting resin system is in a pre-gel state after pre-treatment, thereby avoiding the situation where the pressing density of the obtained soft magnetic composite material is too low due to excessive heating and cross-linking of the thermosetting resin system, so that the soft magnetic composite material can have both higher insulation resistance and pressing density.
[0019] The soft magnetic composite material prepared by the method has a pressing density of 5.60 g / cm 3 ~6.20g / cm 3 , insulation resistance ≥100MΩ@100V.
[0020] Correspondingly, the present invention also provides a soft magnetic composite material, which is prepared by any one of the above-mentioned preparation methods of the soft magnetic composite material and has higher insulation resistance and pressing density.
[0021] Correspondingly, the present invention also provides a molded inductor, which is made of the above-mentioned soft magnetic composite material and has higher insulation resistance and pressing density.
[0022] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. DETAILED DESCRIPTION
[0023] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0025] A method for preparing a soft magnetic composite material comprises the following steps:
[0026] The soft magnetic metal powder and the thermosetting resin system are mixed and granulated to obtain granulated powder.
[0027] The granulated powder is pre-treated so that the state of the thermosetting resin system is between the initial state and the gel state, thereby obtaining the pre-gel state granulated powder.
[0028] The pre-gel granulated powder is subjected to temperature and pressure treatment to obtain a soft magnetic composite material.
[0029] The present invention adds a pretreatment step before the granulation powder is subjected to temperature and pressure treatment. The thermosetting resin system in the granulation powder softens and flows under the action of the pretreatment and undergoes a certain degree of cross-linking reaction, thereby increasing the viscosity of the granulation powder under temperature and pressure treatment conditions and improving the coating effect of the thermosetting resin system on the soft magnetic metal powder, thereby obtaining a soft magnetic composite material with higher insulation resistance. In the present method, the thermosetting resin system is in a pre-gel state after the pretreatment, thereby avoiding the situation where the compression density of the obtained soft magnetic composite material is too low due to excessive heating and cross-linking of the thermosetting resin system, so that the soft magnetic composite material can have both higher insulation resistance and compression density.
[0030] The pre-gel state mentioned in the present invention means that the reaction degree of the thermosetting resin system in the granulated powder is less than the critical gel point. At this time, the viscosity of the pre-gel granulated powder is significantly improved compared with the granulation and / or the pre-gel granulated powder can be transformed into a gel state within 5s-60s at the temperature of the warm pressure treatment.
[0031] In a feasible implementation, the temperature of the pretreatment is 30°C-80°C lower than the temperature of the warm pressure treatment.
[0032] Among them, different thermosetting resin systems correspond to different temperatures of the warm-pressing treatment, and the temperature of the warm-pressing treatment is generally 30° C.-50° C. higher than the reaction peak temperature measured by the DSC curve of the thermosetting resin system.
[0033] When the temperature difference between the pretreatment temperature and the temperature pressing treatment temperature is too small, the pre-gel granulated powder may be converted into a gel state, the degree of cross-linking between the thermosetting resin system is high, and cavities are formed between the cross-linked networks, resulting in a low pressing density of the prepared soft magnetic composite material.
[0034] In a feasible implementation, the thermosetting resin system is bisphenol A cyanate ester and bisphenol A epoxy resin, the pretreatment temperature is 100° C.-140° C., and the pretreatment time is 30 min-120 min.
[0035] When the pretreatment temperature is too low, the viscosity of the pregel granulated powder is too low, and the insulation resistance of the obtained soft magnetic composite material is low; when the pretreatment temperature is too high, the pregel granulated powder is transformed into a gel state, and the pressing density of the obtained soft magnetic composite material is low.
[0036] As the pretreatment time increases, the crosslinking degree of the thermosetting resin system increases, which increases the viscosity of the pregel granulated powder and reduces the pressing density of the soft magnetic composite material. If the pretreatment time is too short, the viscosity of the pregel granulated powder is too low, and the insulation resistance of the obtained soft magnetic composite material is low; if the pretreatment time is too long, the crosslinking degree of the pregel granulated powder is too high, and the pressing density of the obtained soft magnetic composite material is low.
[0037] In a feasible implementation, the temperature of the warm-pressing treatment is 150° C.-200° C., and the time of the warm-pressing treatment is 15s-180s.
[0038] In a feasible implementation, the thermosetting resin system includes a thermosetting resin and a curing agent, wherein the thermosetting resin is selected from at least one of an epoxy resin, a cyanate resin and a linear phenolic resin.
[0039] In a feasible implementation, the soft magnetic metal powder is selected from carbonyl iron powder, reduced iron powder, atomized iron powder, atomized Fe (100-x-y) Si x Cry At least one of powder (x=3.5-6.5, y=0.0-6.5), iron-based amorphous soft magnetic powder, iron-based amorphous nanocrystalline powder, Sandust powder and HighFlux powder.
[0040] In a feasible implementation, the soft magnetic metal powder is a mixture of carbonyl iron powder and iron-based amorphous powder. The small-sized carbonyl iron powder and the large-sized iron-based amorphous powder are mixed to achieve a three-dimensional coating effect after warm pressing treatment, thereby improving the insulation resistance of the soft magnetic composite material.
[0041] In a feasible implementation, before the step of mixing the soft magnetic metal powder and the thermosetting resin system for granulation, the soft magnetic metal powder is subjected to surface insulation treatment. The surface insulation treatment can further block the current path and effectively reduce the eddy current loss of the soft magnetic composite material.
[0042] The present invention also provides a soft magnetic composite material, which is prepared by any one of the above-mentioned soft magnetic composite material preparation methods, and has high insulation resistance and pressing density, and the pressing density is 5.60g / cm 3 -6.20g / cm 3 , insulation resistance ≥100MΩ@100V.
[0043] The present invention also provides a molded inductor, which is obtained by first placing a winding in a mold and then adding the soft magnetic composite material and pressing it, and has higher insulation resistance and pressing density.
[0044] With reference to the above implementation contents, in order to make the technical solution of the present invention more specific, clear and easy to understand, the technical solution of the present invention is now exemplified. However, it should be noted that the contents to be protected by the present invention are not limited to the following Examples 1 to 10.
[0045] Example 1
[0046] 1000 g of carbonyl iron powder with an average particle size of 5 μm was subjected to surface insulation treatment using 2 g of phosphoric acid and 50 g of acetone to obtain passivated carbonyl iron powder.
[0047] 1000 g of an iron-based amorphous powder having an average particle size of 15 μm was subjected to surface insulation treatment using 2 g of phosphoric acid and 50 g of acetone to obtain a passivated iron-based amorphous powder.
[0048] 700 g of passivated carbonyl iron powder, 300 g of passivated iron-based amorphous powder, 24 g of bisphenol A cyanate, 6 g of bisphenol A epoxy resin and 100 g of acetone were mixed and granulated to obtain granulated powder.
[0049] The granulated powder was dried and then pretreated at 100° C. for 30 minutes to obtain a pre-gel granulated powder.
[0050] The pre-gel granulated powder was subjected to a temperature pressing treatment at 180° C. and 200 MPa for 120 seconds to obtain a soft magnetic composite material sample with a size of 10 mm*10 mm*3 mm.
[0051] Example 2
[0052] The difference between Example 2 and Example 1 is that the pretreatment temperature is 110°C.
[0053] Example 3
[0054] The difference between Example 3 and Example 1 is that the pretreatment temperature is 120°C.
[0055] Example 4
[0056] The difference between Example 4 and Example 1 is that the pretreatment temperature is 130°C.
[0057] Example 5
[0058] The difference between Example 5 and Example 1 is that the pretreatment temperature is 140°C.
[0059] Example 6
[0060] The difference between Example 6 and Example 1 is that the pretreatment time is 60 minutes.
[0061] Example 7
[0062] The difference between Example 7 and Example 1 is that the pretreatment time is 120 minutes.
[0063] Example 8
[0064] The difference between Example 8 and Example 1 is that the pretreatment temperature is 130° C. and the pretreatment time is 10 min.
[0065] Example 9
[0066] The difference between Example 9 and Example 9 is that the pretreatment temperature is 140°C.
[0067] Example 10
[0068] The difference between Example 10 and Example 9 is that the pretreatment temperature is 150°C.
[0069] Comparative Example 1
[0070] The difference between Comparative Example 1 and Example 1 is that the pretreatment temperature is 70°C.
[0071] Comparative Example 2
[0072] The difference between Comparative Example 2 and Example 1 is that the pretreatment temperature is 80°C.
[0073] Comparative Example 3
[0074] The difference between Comparative Example 3 and Example 1 is that the pretreatment temperature is 90°C.
[0075] Comparative Example 4
[0076] The difference between Comparative Example 4 and Example 1 is that the pretreatment temperature is 150°C.
[0077] Comparative Example 5
[0078] The difference between Comparative Example 5 and Example 1 is that the pretreatment temperature is 160°C.
[0079] Comparative Example 6
[0080] The difference between Comparative Example 6 and Example 1 is that the pretreatment time is 15 minutes.
[0081] Comparative Example 7
[0082] The difference between Comparative Example 7 and Example 1 is that the pretreatment time is 240 min.
[0083] Comparative Example 8
[0084] The difference between Comparative Example 8 and Example 8 is that the pretreatment temperature is 120°C.
[0085] Comparative Example 9
[0086] The difference between Comparative Example 9 and Example 8 is that the pretreatment temperature is 160°C.
[0087] Comparative Example 10
[0088] The difference between Comparative Example 10 and Example 8 is that the pretreatment temperature is 170°C.
[0089] Performance Test:
[0090] The viscosity and gel time of the pre-gel granulated powder after pretreatment in Comparative Examples 1 to 10 and Examples 1 to 10, as well as the pressing density and insulation resistance of the soft magnetic composite material were tested:
[0091] The viscosity test in the present invention is to test the pre-gel granulated powder after pretreatment by keeping it at 120°C for 2 minutes using a viscometer;
[0092] The gel time in the present invention is tested using a Brookfield gel time tester: 100 ml of pre-gel granulated powder is taken into a sample cup, and a glass rod is immersed in the pre-gel granulated powder, with the end of the glass rod 0.5 inches away from the bottom of the sample cup. The speed is set to 1RPM, the test temperature is 180°C, the viscometer motor is started, the test is started, the changes in viscosity and torque are observed, and the time when the viscosity and torque increase rapidly is recorded, which is the gel time;
[0093] The compaction density in the present invention is tested using a ZMD electronic density meter;
[0094] The insulation resistance in the present invention is tested using a chroma19053 withstand voltage tester, with the voltage set to 100V and the test time being 3s;
[0095] The test results are shown in Tables 1 to 3.
[0096] Table 1 Performance test of comparative examples 1 to 5 and embodiments 1 to 5
[0097]
[0098] Table 2 Performance tests of Comparative Examples 6 to 7 and Examples 1, 6 to 7
[0099]
[0100]
[0101] Table 3 Performance test of comparative examples 8 to 10 and embodiments 8 to 10 (temperature of warm pressing treatment is 180°C)
[0102]
[0103] It can be seen from Table 1 that the compaction density of Examples 1 to 5 can all reach 5.60 g / cm 3 As shown in the above, the insulation resistance is ≥100MΩ@100V; however, in Comparative Examples 1 to 3, the viscosity of the pre-gel granulated powder is too low due to the low pretreatment temperature, which leads to a lower insulation resistance of the soft magnetic composite material; in Comparative Examples 4 and 5, the pretreatment temperature is too high, and the samples have reached a gel state, resulting in a lower pressing density of the soft magnetic composite material, so the pretreatment temperature should be set between 100°C and 140°C.
[0104] It can be seen from Table 2 that the soft magnetic composite materials prepared in Example 1, Example 6 and Example 7 can achieve higher pressing density and insulation resistance; while the pretreatment time of Comparative Example 6 is shorter, and the insulation resistance of the soft magnetic composite material is lower; the pretreatment time of Comparative Example 7 is too long, and the pressing density of the soft magnetic composite material is lower, so the pretreatment time should be set between 30min and 120min.
[0105] It can be seen from Table 3 that the soft magnetic composite materials prepared in Examples 8 to 10 can achieve higher pressing density and insulation resistance; while in Comparative Example 8, due to the large difference between the pressing temperature and the pretreatment temperature, the insulation resistance is low; in Comparative Examples 9 and 10, due to the small difference between the pressing temperature and the pretreatment temperature, the pressing density is reduced.
[0106] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all feasible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0107] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a soft magnetic composite material, characterized in that: The steps include: The soft magnetic metal powder and the thermosetting resin system are mixed and then granulated to obtain granulated powder; Pre-treating the granulated powder so that the state of the thermosetting resin system is between the initial state and the gel state, thereby obtaining a pre-gel granulated powder; as well as Performing a temperature-pressing treatment on the pre-gel granulated powder to obtain a soft magnetic composite material; The viscosity of the pre-gel granulated powder is significantly increased compared to the initial state; The pre-gel granulated powder can be transformed into a gel state within 5s-60s at the temperature of the warm and press treatment; The temperature of the pretreatment is 30°C-80°C lower than the temperature of the warm pressure treatment; The thermosetting resin system is bisphenol A cyanate ester and bisphenol A epoxy resin, the pretreatment temperature is 100° C.-140° C., and the pretreatment time is 30 min-120 min.
2. The method for preparing the soft magnetic composite material according to claim 1, characterized in that: The temperature of the warm-pressing treatment is 150° C.-200° C., and the time of the warm-pressing treatment is 15s-180s.
3. The method for preparing the soft magnetic composite material according to claim 1, characterized in that: The soft magnetic metal powder is selected from carbonyl iron powder, reduced iron powder, atomized iron powder, atomized Fe (100-x-y) Si x Cr y powder, at least one of iron-based amorphous soft magnetic powder and iron-based amorphous nanocrystalline powder; atomized Fe (100-x-y) Si x Cr y In the powder, x=3.5-6.5, y=0.0-6.
5.
4. The method for preparing the soft magnetic composite material according to claim 1, characterized in that: Before the step of mixing the soft magnetic metal powder and the thermosetting resin system for granulation, the soft magnetic metal powder is subjected to surface insulation treatment.
5. A soft magnetic composite material, characterized in that: The soft magnetic composite material is prepared by the preparation method of any one of claims 1 to 4.
6. A molded inductor, characterized in that: The material for preparing the molded inductor includes the soft magnetic composite material according to claim 5.
Citation Information
Patent Citations
Manufacturing method of high magnetoconductivity FcSiAl magnetic powder core
CN101090019A
Gel curing processing method of epoxy resin
CN101837617A